THE PENGARUH DAYA TARIK WISATA, SOSIAL MEDIA DAN PERSEPSI HARGA TERHADAP KEPUTUSAN BERKUNJUNG - Dwika Andreani; Meylani Tuti (Eduturisma, 2022)
There are many things that can be influence of decision to visit. Therefore this study aims to determine the relationship between Tourist Attraction, Social Media and Price Perception on Visiting Decisions. This study was conducted on visitor to the Rumah Guguk, Rabbit Town and Dago Dream Park in Bandung as many 250 respondents with accidental sampling. The analysis method used SEM analysis using Smart-PLS for analyzing and developing the model. The outcome of the analysis revealed that all three hypotheses were supported. These findings will assist for the development of Rumah Guguk, Rabbit Town and Dago Dream Park. This study explores the relationship amang Tourist Attraction, Social Media and Price Perception on Visiting Decisions.